Socio-Economic Status of Dalits of the Western Tarai Villages, Nepal - Kareriya, Bhoj Raj (Geographical Journal of Nepal, 2011)
Doms or Dalits living in Tarai region of Nepal are categorized as untouchable according to the Hindu caste system. In other words, they are also defined economically exploited, politically voiceless, socially humiliated, and educationally backward and treated as untouchable castes in the Nepalese Constitution, 2063BS. In the present paper both primary and secondary sources of data have been used. Four VDCs such as Akala, Basantpur, Kamahariya, and Sadi of Rupandehi district have been selected purposively based on the relative representation of the dalits. Altogether 30 Dom households were selected randomly. The paper focuses mainly on analyzing socio-economic condition of the Dom communities and major problems faced by them for livelihoods and at the end, suggestions are provided to raise their living standard. The Geographical Journal of Nepal, Vol. 8-9, 2010-2011: 13-22